2012
DOI: 10.1039/c2jm15561c
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline silicon carbide thin films by fluidised/packed bed chemical vapor deposition using a halogen-free single source

Abstract: Thermal stability, vapor pressure, and binary gaseous diffusion coefficients of organosilanes were studied at temperatures in the range of 309-507 K in ambient pressure. The temperature dependence equilibrium vapor pressure (p e ) T data yielded a straight line, when ln p e was plotted against the reciprocal temperature, leading to a standard enthalpy of sublimation (D s H ) values of 43.3 AE 0.6, 68.2 AE 0.8 and 72.4 AE 0.6 kJ mol À1 for 1,4-bis(trimethylsilyl)butadiyne (TMSBu), 1,4bis(trimethylsilyl)benzene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Recently, we have successfully demonstrated SiC deposition with the combined approach of FB sublimator and fluidized/packed bed CVD process using solid 1,4-bis(trimethylsilyl)benzene as single source. 33 The FB technique confirmed that the 1,4-bis (trimethylsilyl)benzene vapor of the solid source can be effectively carried with high precursor flux in a consistent and controlled manner for CVD use. The obtained orientations, degrees and size of crystallinity, good uniformity, and better thickness with growth rate of the SiC film reveal that SCHEME 4.…”
Section: Call For Alternative Cvd Sources For Sic Depositionsupporting
confidence: 52%
See 1 more Smart Citation
“…Recently, we have successfully demonstrated SiC deposition with the combined approach of FB sublimator and fluidized/packed bed CVD process using solid 1,4-bis(trimethylsilyl)benzene as single source. 33 The FB technique confirmed that the 1,4-bis (trimethylsilyl)benzene vapor of the solid source can be effectively carried with high precursor flux in a consistent and controlled manner for CVD use. The obtained orientations, degrees and size of crystallinity, good uniformity, and better thickness with growth rate of the SiC film reveal that SCHEME 4.…”
Section: Call For Alternative Cvd Sources For Sic Depositionsupporting
confidence: 52%
“…The representative microstructure of the FB SiC material is summarized elsewhere. 33 Scheme 1 shows the microstructure of multiple coatings on a UO 2 kernel fabricated using the FB CVD process. The lowdensity buffer layer of PyC is obtained by the decomposition of acetylene (C 2 H 2 ) at temperatures ranging from 1573 to 1673 K with the density controlled by the gas concentration and temperature.…”
Section: Sic: Development and Techniquesmentioning
confidence: 99%
“…Furthermore, we proposed another method to prepare porous SiC coating layer by using nonchloric reactant. There were also some halogen-free precursors for preparing SiC material, such as SiC films [21] and SiC layers [22], using chemical vapor deposition method. In this work, HMDS was used to prepare the porous SiC layer instead of MTS, which is called HMDS method.…”
Section: Hmds Methodsmentioning
confidence: 99%
“…Using a single source precursor offers the advantages of having a less complicated CVD system and working at low deposition temperatures. 16 These SiC coated Si wafers behave as a junction due to large difference in band-gap between Si and SiC. The I-V characteristics show a high reverse breakdown voltage and a low cutin voltage.…”
Section: Introductionmentioning
confidence: 99%